2015
DOI: 10.1002/bdm.1880
|View full text |Cite
|
Sign up to set email alerts
|

Cautious Defection: Group Representatives Cooperate and Risk Less than Individuals

Abstract: Individuals often make decisions that affect groups, yet the propensities of group representatives are not as well understood than those of independent decision makers or deliberating groups. We ask how responsibility for group payoffs-in the absence of group deliberation-affects the choice. The experiment utilizes the Interdependent Security Dilemma paradigm. In its deterministic version, the game is identical to a finitely repeated Prisoner's Dilemma. In the stochastic version, potential losses are larger bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Extensive research has found that monetary allocation affects individuals' choices in decision making (e.g., Atanasov & Kunreuther, 2016; Sutter, 2009). This research focused on how monetary allocation in a two‐person context described to the decision makers affected their decisions, especially when the final outcome was consistent across conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has found that monetary allocation affects individuals' choices in decision making (e.g., Atanasov & Kunreuther, 2016; Sutter, 2009). This research focused on how monetary allocation in a two‐person context described to the decision makers affected their decisions, especially when the final outcome was consistent across conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Decision makers tended to make riskier choices in the self‐allocation frame than in the other‐allocation frame. The other‐allocation frame, such as the practice of incentivizing agents, has been studied (Atanasov & Kunreuther, 2016; Pahlke et al, 2015). Similarly, the self‐allocation condition can also be found in daily life, such as in decisions made by a single person in a partnership system, but according to our review of the literature, has been underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Such tasks are cognitively complex, have lower test–retest stability, and produce greater noise in the data, especially for individuals with lower math ability (Dave, Eckel, Johnson, & Rojas, ). Furthermore, hypothetical options have little real consequence for the decision maker, although one or a few decisions were extracted to be played for real payment in some research (e.g., Andersson et al, ; Atanasov & Kunreuther, ; Pahlke et al, ). In contrast, the present research used three laboratory‐based behavioral measures of risk taking (BART, Lejuez et al, ; Marble Risk Task, Frankenhuis & Karremans, ; one‐shot gambling task).…”
Section: Discussionmentioning
confidence: 99%
“…As the decision is often ultimately left to one person (i.e., the representative), there is little chance for the decision maker to pass on the responsibility. Some previous research suggests that a sense of responsibility increases risk aversion (e.g., Anderson & Galinsky, 2006;Atanasov & Kunreuther, 2016;Charness & Jackson, 2009). In a classic study, Wallach and Kogan (1965) showed that individuals became more risk seeking when decisions were made following group discussions (i.e., risk-shift phenomenon).…”
mentioning
confidence: 99%
“…However, employing agents in negotiations also comes with undeniable costs. Agents may have goals that conflict with those of their principals (Aaldering, Greer, Van Kleef, & De Dreu, ; Eisenhardt, ); they are often reluctant to admit their biases (Northcraft & Neale, ); and they tend to be swayed by competitive directions more than by cooperative directions (Atanasov & Kunreuther, ; Steinel, De Dreu, Ouwehand, & Ramirez‐Marin, ).…”
mentioning
confidence: 99%